Attracting Undergrads: A study of effective advertising for a virtual-visual generation - Washburn, Allyson; Bibb, Sheila C. (Qualitative and Quantitative Methods in Libraries, 2017)
Through a series of studies, an applied anthropology class, their professor, and a librarian joined forces to learn about student use and awareness of the library, focusing on the gaps between expressed student needs, their use of library materials and services, and what the library has to offer. In spite of efforts to educate them, many students remain unaware of what is available.  Building on the idea that the library needs to respond to the behavior of users, a study undertaken in 2011 focused on what university students considered the best means and locations to advertise and disseminate library information.  We posit that our behavior as a library can influence student behavior if we market and advertise using methods to which students respond.